2005
DOI: 10.1007/s00127-005-0908-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact of family experience on the duration of untreated psychosis (DUP) in Hong Kong

Abstract: In addition to the mode of onset, previous family experience plays an important role in the presentation of early psychosis. Educational efforts that target the family should be an important part of any strategy for the early detection of psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…In line with the former hypothesis, Norman et al (2007) discovered that the presence of a FH of psychosis is associated with a longer DUI (but not shorter DUP). In line with the latter hypothesis that FH is associated with a shorter DUP, Chen et al (2005) found that FH of psychiatric illness was a significant predictor of a shorter DUP.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…In line with the former hypothesis, Norman et al (2007) discovered that the presence of a FH of psychosis is associated with a longer DUI (but not shorter DUP). In line with the latter hypothesis that FH is associated with a shorter DUP, Chen et al (2005) found that FH of psychiatric illness was a significant predictor of a shorter DUP.…”
Section: Discussionsupporting
confidence: 67%
“…While the current study is similar to the previous studies in several ways (e.g., FEP patient samples, large sample sizes, and similar operationalizations of DUI/DUP), there are several important methodological differences. First, our study utilized a strict definition of FH that was defined as the presence of a non-affective psychotic disorder in a first-degree relative of the patient, whereas both Chen et al (2005) and Norman et al (2007) included both first- and second-degree relatives. Second, the current study focused only on the presence of psychosis in family members, whereas Chen et al (2005) included any psychiatric illness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Remission was assessed using the modified GAF [13] based on careful case-note review with the responsible clinician. The duration of psychosis was assessed according to the Interview for the Retrospective Assessment of the Onset and Course of Schizophrenia [25,26]. This study was approved by the hospital Institutional Review Board and was performed in accordance with the ethical standards laid down in the 1964 Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%